Sonification in swimming - Hermann, T.; Ungerechts, B. (2016)
Sonification is the systematic and reproducible representation of data by using non-speech sound, the auditory counterpart to visualization. In this project, we develop sonification systems that represent the interaction of the human body with water to render relevant information for the swimming technique auditory salient for both the swimmer and the trainer. As important source of information we connect to the hydrodynamic pressure at selected points on the human body (e.g. hand, feet, etc.) and thus enable swimmers to improve their `feel for water`. In contrast to merely kinematic (posture) or dynamic (forces) information, the surrounding hydrodynamic field provides an intermediate effect of the swimmer`s actions the awareness of which can be of eminent importance to attain a more effective swimming technique. The sonification is played both for the swimmer (via in-ear headphones) and to the coach, so that the sonification also offers an innovative new medium for coaching interactions: referring to the sound, the coach could direct the swimmers` attention to specific phenomena (e.g. saying "try to modify your movements so that the sound sustains longer or starts faster"). On the other side, the swimmer can immediately use the sound as feedback for their own activity. Our approach is the first interactive sonification involving pressure measurements which is tested interactively in the pool. It has been explored by top-class swimmers in a practical workshop and published in international conferences on both auditory display and swimming sports research.